Determining the rational number of spindles on the drum of a vertical spindle cotton harvesting apparatus - Omonov N.N., Sherqobilov S.M.; Omonov N.N., Sherqobilov S.M. (International Journal of Advanced Science and Technology, 2020)
The article deals with the issues of increasing productivity and improving the currently produced cotton harvesters, as well as scientific and technical developments which are carried out in this direction. The analysis of researches carried out in this direction is presented. The equation of a spindle axis trajectory, schemes and influencing factors for definition of a degree of processing by spindles of a row of cotton bushes, definition of an entrance point of a spindle to the bushs row, expression of possibility of definition of number of spindles on a spindle drum, the schedule of dependence of number of spindles on a spindle drum of a vertically spindle cotton-harvesting machine from working speed are resulted, description of the tests carried out by fourteen spindle drums installed on a vertical spindle cotton harvesting machine series MX-1.8 in cotton fields, the results of laboratory and field tests, as well as the introduction of the developed technical solutions are given..